NATIONAL EDUCATION POLICY 2020 : PROMISES AND PROSPECTS FOR HIGHER EDUCATION IN INDIA - Chopra, Rajiv; Pandey, Srikant (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The National Education Policy 2020( NEP 2020) which is the third policy document on education since independence is based on the objective of restructuring/ revamping the education system so that it can act as a catalyst for laying down the foundations/ roadmap of a new India/ Vikshit Bharat . Approved by the cabinet/ government of India on 29th July 2020 it aims at giving a big thrust/ boost to higher education in India by adopting progressive/ reformatory path of bringing about required qualitative changes not only in the existing model of education but the system of governance as well. In fact this visionary document is an ambitious manifesto of scaling the heights of global leadership. Having a firm understanding of the contemporary fast evolving socio-economic situation and the potential for addressing the possible challenges of the future it can transform India into a global hub of education by 2030 provided the implementation matches the prescribed principles. The researcher is primarily focused on the secondary sources/ review of available / existing literature which are used to explain , examine and evaluate the problems and prospects of NEP 2020 in a descriptive manner.